2020
DOI: 10.3390/bs10050091
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Personality Traits of Teachers in Risk Conditions due to Work-Related Stress

Abstract: The following study aims to verify whether psychosocial risk conditions determine a variation in personality traits. The sample consisted of 301 teachers, comprising 84 men (27.1%) and 217 women (72.9%). The Big Five Questionnaire (BFQ) was used to measure personality traits, while the Organizational and Psychosocial Risk Assessment (OPRA) questionnaire was used to measure psychosocial risk. The ANOVA results notice the change of BFQ traits. These are significant (Extraversion = 0.000; Agreeableness = 0.001; N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Patients have previously indicated that they believe that surgeon personality influences surgical decision-making (including informed consent and communication of treatment options) as well as the surgeon’s response to post-operative complications [ 40 ]. Whilst we do not advocate personality testing as a recruitment strategy for trainee selection, the authors hypothesise that periodic personality testing of surgeons throughout their career (given that personality changes with age and experience) may facilitate continuing professional development via multiple methods, for example, targeted non-technical skills training for surgeons, and also aid identification of surgeons at risk of work-related stress or burnout with timely occupational health interventions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients have previously indicated that they believe that surgeon personality influences surgical decision-making (including informed consent and communication of treatment options) as well as the surgeon’s response to post-operative complications [ 40 ]. Whilst we do not advocate personality testing as a recruitment strategy for trainee selection, the authors hypothesise that periodic personality testing of surgeons throughout their career (given that personality changes with age and experience) may facilitate continuing professional development via multiple methods, for example, targeted non-technical skills training for surgeons, and also aid identification of surgeons at risk of work-related stress or burnout with timely occupational health interventions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This issue and the closely related themes had been numerously researched in ECE analyses before in other places of the world and in various social conditions with the use of both quantitative and qualitative strategies of social research (see, e.g. Andrisano Ruggieri et al, 2020;Aziz, Quraishi, 2017;Beatty, 2011;Christensen, 2016;Christensen, 2019;Efe, Ulutas, 2022;Ender, Ozcan, 2019;Malm, 2004;Siswanto, Kuswandono, 2020). It is undoubtedly a significant problem as it has the potential to -in Goffman's terms -"frame" experiences and practices (Bavli, Kocabaş, 2022;Damore, Rieckhof, 2021) not only with regard to ECE, but also in relation to the teacher trainees (Slovacek, Minova, 2021), high school Montessori education (Rathunde, Csikszentmihalyi, 2005) and other "alternative" pedagogies (Dodd-Nufrio, 2011).…”
Section: Methodsmentioning
confidence: 99%